2010
DOI: 10.4321/s1699-695x2010000200008
|View full text |Cite
|
Sign up to set email alerts
|

Estudio sobre Automedicación en Población Universitaria Española

Abstract: RESUMENObjetivo. La automedicación es una práctica común en diferentes sociedades que puede tener importantes implicaciones sanitarias. Esta práctica ha sido poco estudiada hasta ahora en población universitaria española. Nuestro objetivo es cuantificar esta actividad y estudiar los factores asociados a la misma. Material y método. Se diseñó y facilitó un cuestionario para su autocumplimentación a una muestra de población universitaria. Se evaluó el impacto de tres variables principales sobre la automedicación… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
11
3
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 13 publications
8
11
3
12
Order By: Relevance
“…Self-medication is very common in this Colombian population according to this study, which revealed that at least three quarters of the people have self-medicated at least once in their life and one third during the month prior to the survey. These results are similar to those reported in Colombia (77.5% vs. 21.8-97.0%) (12)(13)(14) and globally (77.5% vs. 14.0-90.8%) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)15).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Self-medication is very common in this Colombian population according to this study, which revealed that at least three quarters of the people have self-medicated at least once in their life and one third during the month prior to the survey. These results are similar to those reported in Colombia (77.5% vs. 21.8-97.0%) (12)(13)(14) and globally (77.5% vs. 14.0-90.8%) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)15).…”
Section: Discussionsupporting
confidence: 80%
“…There are few studies that have looked at a whole city, and the numbers reported by local and international studies show a wide variability influenced by a variety of factors including variables measured and differences in population characteristics (students, children, pregnant women or elderly population), as well as use of different drug groups and period over which self-medication was reported (lifespan or a defined period of time) that complicate data comparison (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations